Predicted temperature-increase-induced global health burden and its regional variability. (October 2019) - Lee, Jae Young; Kim, Ho; Gasparrini, Antonio; Armstrong, Ben; Bell, Michelle L.; Sera, Francesco; Lavigne, Eric; Abrutzky, Rosana; Tong, Shilu; Coelho, Micheline de Sousa Zanotti Stagliorio; Saldiva, Paulo Hilario Nascimento; Correa, Patricia Matus; et al.
Abstract: An increase in the global health burden of temperature was projected for 459 locations in 28 countries worldwide under four representative concentration pathway scenarios until 2099. We determined that the amount of temperature increase for each 100 ppm increase in global CO2 concentrations is nearly constant, regardless of climate scenarios. The overall average temperature increase during 2010–2099 is largest in Canada (1.16 °C/100 ppm) and Finland (1.14 °C/100 ppm), while it is smallest in Ireland (0.62 °C/100 ppm) and Argentina (0.63 °C/100 ppm). In addition, for each 1 °C temperature increase, the amount of excess mortality is increased largely in tropical countries such as Vietnam (10.34%p/°C) and the Philippines (8.18%p/°C), while it is decreased in Ireland (−0.92%p/°C) and Australia (−0.32%p/°C). To understand the regional variability in temperature increase and mortality, we performed a regression-based modeling. We observed that the projected temperature increase is highly correlated with daily temperature range at the location and vulnerability to temperature increase is affected by health expenditure, and proportions of obese and elderly population. Highlights: Future health burden with respect to CO2 increase was projected in 28 countries. Future temperature and mortality were compared across locations. Daily temperature range determines the rate of temperature increase. Amount of health expenditure determines the vulnerability to temperature change.